Towards Optimal Heart Failure Care: Couples-Oriented Strategies to Improve Patient Adherence and Health Outcomes - R. Toukhsati, Samia; L. Hare, David (Current Cardiology Reviews, 2016)
Psychosocial factors play an important role in the development and progression of cardiovascular diseases (CVD), such as chronic heart failure (CHF). In particular, psycho-cognitive disturbance is common in CHF, which presents additional challenges to secondary prevention and management strategies. This review provides a summary of the contemporary psycho-cardiology literature, including coverage of common mood and cognitive symptoms, and explores some of the pathophysiologic evidence linking psycho-cognition to CHF, with particular emphasis on sympathetic nervous system activation and neuroendocrine functioning. Social support is identified as a strategy by which to reduce depressive symptoms, manage cognitive impairment and to, potentially, improve health outcomes through improved patient self care and adherence. Recent research outcomes suggest that the integration of family caregivers into CHF psycho-educational disease management programs, as providers and recipients of support, may achieve best outcomes. In this regard, couples-oriented strategies that promote communication, emotional attachment and support may enhance healthpromoting behaviours in patients and their partners.
Keywords: Social support